DETERMINATION OF PROFESSIONALISM AND TRANSPARENCY AND ITS IMPLICATIONS FOR THE FINANCIAL PERFORMANCE OF ZAKAT INSTITUTIONS - Rifzaldi Nasri; Nur Aeni; Marissa Grace Haque-Fawzi (Journal of Islamic Monetary Economics and Finance, 2019)
The objective of this study is to determine the influence of the professionalism and transparency of zakat management on financial performance, especially in the case of the Amil Zakat Institution of Daarut Tauhid Peduli Jabodetabek. The method used in the research is SEM (structural equation modeling) using AMOS, with 156 respondents. The results show that: (1) professionalism has a negative and insignificant impact on the transparency of zakat management; (2) professionalism has a positive and significant impact on financial performance; and (3) the transparency of zakat management has positive and significant impacts on financial performance. Moreover, the indicators of competence have the highest loading factors of professionalism; the indicator of information on fund management has the highest loading factors of transparency; while the indictor of measurement of economics has the highest loading factor of financial performance. To sum up, this research suggests that zakat institutions should improve their transparency and professionalism in order to improve their financial performance in the future.